Development Models, Challenges, and Emerging Trends of Digital Procurement in China - Zhou, Tianlan; Yu, Hongyan (Journal of Global Economy, Business and Finance, 2025)
The rapid growth of the digital economy and intelligent manufacturing has made digital procurement a key driver of supply chain transformation. While advanced economies have widely adopted artificial intelligence, big data, the Internet of Things, and blockchain to improve efficiency and transparency, China continues to face challenges in system integration, data security, and talent readiness. This paper addresses these gaps by examining the evolution, constraints, and optimization pathways of digital procurement in China. Drawing on policy documents, industry reports, case studies, and secondary literature, the study reviews national strategies, technological drivers, and industrial applications. The findings show that government initiatives and technological innovation create significant opportunities, especially in rapidly upgrading sectors such as new energy vehicles, logistics, and healthcare. Yet major obstacles persist, including fragmented platforms, insufficient training, and heightened risks from global uncertainties such as trade barriers and supply chain restructuring. Case analyses demonstrate that integrated collaboration platforms, business-value-oriented reforms, and digitally enabled supplier management can enhance transparency, reduce costs, and strengthen resilience. This study contributes by systematically mapping the trajectory of digital procurement in China, identifying internal and external constraints, and outlining a strategic roadmap to guide enterprises and policymakers in advancing digital–intelligent supply chain transformation.